Analysis of the postural stabilization in the upright stance using optimization properties. (July 2019) - Porto, Carla; Lemos, Thiago; Ferreira, Arthur Sá
Highlights: Postural stabilization while standing can be analyzed with optimization properties. The center-of-pressure act as a cost-function for optimizing the body's stability. The downhill, stability and convergence properties can be observed in posturography. Sensorial, biomechanical and cognitive constraints affect the optimization process. Abstract: Background: This study investigated the whole-body stability dynamics during upright stance by applying a set of variables characterizing the mathematical optimization process that minimizes the postural sway as a cost-function. Method: The downhill, stability, and convergence properties of postural sway were quantified by implementing a direct pattern search of downhill epochs, and locally and globally optimum valleys using the center-o-pressure (CoP) displacement vector as cost-function. The proposed pattern search was tested using a computational simulation of nine benchmark functions and subsequently applied to posturography data of 94 healthy young individuals collected under vision, support base, and attentional task constraints. Results: Our findings show that visual, supporting, and attentional constraints demand: (1) a faster search for local optimal valleys and a shorter overall time for recovery after a transient increase in CoP displacement; (2) a shift in the expected local optimal valley to higher values with increased variability and decreased local optimum values; and (3) a higher optimal cost-function value with a higher difference from the expected local valleys. Discussion: We found supporting evidence to the hypothesis that visual, supporting, and attentional constraints affect the downhill, stability and convergence properties when attaining to stabilize the whole-body in the upright stance. A harder optimization problem is posed to the postural control system when individuals attained to stabilize the whole-body under task constraints in an independent and combined manner.